The Effects of High-Voltage AC Transmission Lines on Buried Pipelines - Peabody, A. W.; Verhiel, Adrian L. (IEEE transactions on industry and general applications, 1971)
Electrical interference problems will result on pipelines laid in joint use rights-of-way or laid in close proximity with overhead ac transmission lines or substation facilities. Some of the interference problems are discussed and practical solutions are given on how to minimize or nullify the effects.